Hypoglycemia detected during cardiac arrest of a non-diabetic patient with heart failure - İnci Tuğçe Çöllüoğlu; Hüseyin Dursun; Mete Yılmaz; Asım Oktay Ergene (KARE Publishing, 2015)
Hypoglycemia in non-diabetic patients with heart failure is a rare finding. It is thought to be caused by hepatic dysfunction secondary to chronic passive congestion, and reduced gluconeogenesis. In this report we present a 23-year-old man with a history of Duchenne muscular dystrophy hospitalized for decompensated heart failure and implantable cardioverter defibrillator shock. Laboratory examination on admission showed slightly elevated levels of hepatic enzymes. Despite the therapy for heart failure the patient's clinical status deteriorated, and sinus bradycardia and then cardiac arrest occured. After successful 5-minute cardiopulmonary resuscitation, an arterial blood sample revealed metabolic acidosis with a level of pH 7.04, bicarbonate 9.3, and glucose of 22 mg/dl. Acute treatment of metabolic acidosis with hypoglycemia was successfully performed. Based on this case, possible causes of unexplained hypoglycemia in non-diabetic patients with heart failure were described in a short literature review.